The Child Health Myths in NuvO Family Soap Poster: (Roland Barthes Semiotic Analysis) - Salamah, Khoirina Nur (Fakultas Ushuluddin Adab dan Dakwah IAIN Metro-Lampung, 2023)
The health of children is something that parents really hope for. Parents always try to do and give anything to maintain the health of their children. Various safeguards are carried out, one of which is by looking for products that are considered capable of working in improving the health of families, especially children. Advertisements or product posters are starting to get crowded with healthy claims, especially when disease is spreading and knows no age in attacking humans. A poster is always displayed with pictures and words as short as possible but able to cover any form of message to be conveyed. The pictures and words used in the posters must have certain meanings which are expressed through the signs attached to the object in the form of images or words. This research is a qualitative research using Roland Barthes' semiotic analysis method which is considered to be able to explain signifier, signified, and sign in terms of convincing the audience on the myth of children's health built by the Nuvo Family soap poster. Keywords: Children's health, posters, Nuvo Family soap, Roland Barthes semiotics.